Reviewer Acknowledgements for Journal of Biology and Life Science, Vol. 14, No. 1 - Lee, Kelvin (Journal of Biology and Life Science, 2023)
Journal of Biology and Life Science (JBLS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JBLS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 14, Number 1 Arshia Tabassum, University of Karachi, Pakistan Bratko Filipic, (CIETO), Slovenia Hoe Yin Chen, Tunku Abdul Rahman University College, Malaysia Homyra Tasnim, Louisiana State University, Bangladesh Memoona Ramzan, University of Miami, USA Natalia Tkachuk, T.H. Shevchenko National University “Chernihiv Colehium”, Ukraine Ragab A. El-Mergawi, National Research Centre, Egypt Rajaa Ahmed Mahmoud, University of Basrah, Iraq Sridhar Mandali, UCLA, USA Xiaohuang Cao, Guangdong Ocean University, China Kelvin Lee Editorial Assistant Journal of Biology and Life Science ------------------------------------------- Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Tel: 1-702-953-1852 ext.510 Fax: 1-702-420-2900 E-mail 1: jbls@macrothink.org E-mail 2: jbls@macrothink.com URL: http://jbls.macrothink.org